2012
DOI: 10.5336/medsci.2011-22902
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Substances Used for Prevention of Intra-Abdominal Adhesions: An Experimental Study in Rats

Abstract: Ö ÖZ ZE ET T A Am ma aç ç: : Cerrahi sonrası karın içi yapışıklığı önlemek için şimdiye kadar birçok madde denenmiştir. Bu sorun araştırmacıların önünde bir 'bulmaca' olarak halen durmaktadır. Deneysel ameliyat sonrası yapışıklık modelinde çeşitli yapışıklık önleyici maddeleri karşılaştırmayı amaçladık. G Ge er re eç ç v ve e Y Yö ön nt te em ml le er r: : Otuz beş dişi Sprague-Dawley sıçan beş eşit gruba ayrıldı. Laparatomi sonrası, periton ve çekum, nokta nokta kanama görülene kadar diş fırçası ile fırçaland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Peritoneal lavage, although previously attempted in the treatment of intra-abdominal infections and adhesions, does not have precise results. Various studies [4,13,14] have reported the use of saline, antibiotic and fibrinolytic agents given during peritoneal lavage. Today, there is no universally accepted peritoneal lavage method and solution.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal lavage, although previously attempted in the treatment of intra-abdominal infections and adhesions, does not have precise results. Various studies [4,13,14] have reported the use of saline, antibiotic and fibrinolytic agents given during peritoneal lavage. Today, there is no universally accepted peritoneal lavage method and solution.…”
Section: Discussionmentioning
confidence: 99%
“…The histological sections were examined for the presence of periserozal inflammation, fibroblastic activity and foreign body reaction with a light microscope (Nikon Optiphot, Kanagawa, Japan) and photographed. In histopathological evaluation, the previously defined criteria defined by Gunaydın et al were used [14].…”
Section: Histopathological Evaluationmentioning
confidence: 99%
“…Other reports indicate that peritoneal lavage promotes adhesion formation, as opposed to reports that suggested a preventive role for peritoneal lavages in adhesion formation. [26][27][28] Antibiotics can exert their anti-adhesive effects by inhibition of synthesis or expression of adhesins on the bacterial cell surface, or modify bacterial protein expression in such a way as to interfere with the ability of the microorganisms to approach receptors on animal cell surface. [29] Sortini et al [5] compared the efficacy of peritoneal lavage with chloramphenicol, clindamycin, piperacillin, tobramycin, ceftriaxone and imipenem-cilastatin to saline, with adhesion formation increased in study groups.…”
Section: Discussionmentioning
confidence: 99%